2011
DOI: 10.1016/j.ejps.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Engineering tenofovir loaded chitosan nanoparticles to maximize microbicide mucoadhesion

Abstract: The objective of this study was to engineer a model anti-HIV microbicide (Tenofovir) loaded chitosan based nanoparticles (NPs). Box-Behnken design allowed to assess the influence of formulation variables on the size of NPs and drug encapsulation efficiency (EE%) that were analyzed by dynamic light scattering and UV spectroscopy, respectively. The effect of the NPs on vaginal epithelial cells and Lactobacillus crispatus viability and their mucoadhesion to porcine vaginal tissue were assessed by cytotoxicity ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 68 publications
7
83
0
Order By: Relevance
“…The chitosan formulation presented a high potential for the release of antimicrobial agents due to controlled release, bioadhesion, and safety. 23 The incorporation of nanostructured systems, such as nanocapsules, into chitosan gels represents the unification of different systems with interesting properties, as previously mentioned. The incorporation of Eudragit ® RS 100 nanocapsules (Evonik Industries AG, Essen, Germany) in chitosan hydrogels and the controlled-release property of the formulation has already been described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chitosan formulation presented a high potential for the release of antimicrobial agents due to controlled release, bioadhesion, and safety. 23 The incorporation of nanostructured systems, such as nanocapsules, into chitosan gels represents the unification of different systems with interesting properties, as previously mentioned. The incorporation of Eudragit ® RS 100 nanocapsules (Evonik Industries AG, Essen, Germany) in chitosan hydrogels and the controlled-release property of the formulation has already been described.…”
Section: Introductionmentioning
confidence: 99%
“…2 The use of chitosan vehicles and nanoparticles for vaginal delivery have been reported by some scholars. 3,4,23 For instance, hydrogels formed by chitosan derivatives have shown higher adhesion to pig vaginal mucosa than a commercial gel. 3 The citrate salt of chitosan has been proven to be suitable for the preparation of gels incorporating substances with low permeation potential for vaginal administration.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Among polycations, it has received considerable attention for its safety-recent studies have shown that chitosan and its derivatives had no cytotoxic effect on vaginal epithelial cells. 11,12) Chitosan is also reported to show penetration enhancement properties by improving the active agent transport through epithelium layer containing tight junctions. 12) In addition, it possesses antibacterial and antifungal activity 13) and due to its good mucoadhesive properties resulted from the cationic behaviour and the presence of free hydroxyl and amine groups enabling polymer to interact with mucin by hydrogen and electrostatic bonding-chitosan is regarded as a suitable excipient to prepare buccal and vaginal dosage forms.…”
Section: -7)mentioning
confidence: 99%
“…One demonstrate chitosan nanoparticle as a potential microbicide delivery system with a safe bioadhesive and control release properties [223]. In another approach, Belletti and coworkers investigated tenofovir loaded nanoparticle of chitosan and/or poly-(d,l-lactide-coglycolide) (PLGA).…”
Section: Prevention Of Human Immune Deficiency (Hiv) Virus Infectionmentioning
confidence: 99%